DEETI & IBIS SHIP: THE MATAPHORS IN THE FICTION ‘SEA OF POPPIES’ WRITTEN BY AMITAV GHOSH - Vasava, Dilipbhai J. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Sea of Poppies is a description of colonialism and its effect on the environment. The fiction deals with the cultivation of opium and its harmful effect on the life of the people and the environment. Ghosh tries to find out realty behind every historical moment through imaginative characters. The author writes a story of ‘opium war’ and describes difficult times. In the fiction, Amitav Ghosh describes social evils, identity crisis, and caste system. He talks about culture, suffering, struggle, capitalism, race and people in a metaphorical manner. Ghosh describes charater of Deeti, ibis ship as metaphor in the fiction. The imaginative character of Deeti by Amitav Ghosh shows journey from slavery to independence.